Ultrasound assisted synthesis of a zinc(II) coordination polymer with nano-flower morphology and the use as precursor for zinc(II) oxide nanoparticles. (15th November 2018) - Li, Jun-Xuan; Li, Yue-Hua; Qin, Zhan-Bin; Dong, Gui-Ying
Graphical abstract: Nanostructures of a Zn(II) coordination polymer was synthesized by a sonochemical method. CP1 exhibits a 4-connectedmog topology with the topological point symbol of {4.6 4 .8}2 {4 2 .6 2 .8 2 }, which represents a 3-fold interpenetrating structure. Effects of the initial reagent concentrations, sonication time and ultrasonic power on the morphology and size of nanoparticles were also studied. Moreover, the photocatalytic studies indicate that nano1 is an active photocatalyst for the degradation of methylene blue under UV light irradiation. Also, nano1 was used for preparation of ZnO nanoparticles. Abstract: A 3D Zn(II) coordination polymer (CP) {[Zn(L)0.5 (1, 4-bib)]·H2 O} n (1 ), (H4 L = 1, 2, 4, 5-cyclohexanetetracarboxylic acid, 1, 4-bib = 1, 4-bis(1H-imidazol-1-yl)benzene) with flower-like morphology was synthesized under ultrasonic irradiation and characterized by elemental analysis, IR, powder X-ray diffraction and scanning electron microscopy. CP1 exhibits a 4-connected 3-fold interpenetratingmog framework. The thermal stability and luminescence properties of nano1 were investigated. Moreover, nanostructures of zinc(II) oxide were obtained by calcination of nano1 at 600 °C under air atmospheres. Further, nano1 shows a remarkable photocatalytic activity for degradation of MB under UV irradiation, a possible photocatalytic mechanism is proposed in terms of the HOMO–LUMO gap and the associated UV light-induced transitions in the compound.